2005
DOI: 10.1073/pnas.0502187102
|View full text |Cite
|
Sign up to set email alerts
|

Induction of CD4+CD25+regulatory T cells by copolymer-I through activation of transcription factor Foxp3

Abstract: Copolymer-I (COP-I) has unique immune regulatory properties and is a treatment option for multiple sclerosis (MS

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
156
0
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 257 publications
(166 citation statements)
references
References 46 publications
8
156
0
2
Order By: Relevance
“…In vivo tracking of proliferation after adoptive cell transfer rather indicate that treatment led to increased frequencies of FoxP3+CD4+ regulatory T cells, which are known to play a central role in immune modulation (Chen et al, 2003;Fantini et al, 2004;Ng et al, 2013;Mohammadnia-Afrouzi et al, 2015). Similarly, it has been described that in vitro incubation of human CD4+ T cells with a random polymer found in the myelin basic protein, copolymer I, can lead to FoxP3 expression, though in a non antigen-specific manner (Hong et al, 2005). Likewise, expansion of FoxP3 regulatory cells was found to be associated with protection against diabetes induced by multimerized epitopes (Piaggio et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…In vivo tracking of proliferation after adoptive cell transfer rather indicate that treatment led to increased frequencies of FoxP3+CD4+ regulatory T cells, which are known to play a central role in immune modulation (Chen et al, 2003;Fantini et al, 2004;Ng et al, 2013;Mohammadnia-Afrouzi et al, 2015). Similarly, it has been described that in vitro incubation of human CD4+ T cells with a random polymer found in the myelin basic protein, copolymer I, can lead to FoxP3 expression, though in a non antigen-specific manner (Hong et al, 2005). Likewise, expansion of FoxP3 regulatory cells was found to be associated with protection against diabetes induced by multimerized epitopes (Piaggio et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…It remains unclear precisely how CD4 1 CD25 1 Foxp3 1 Treg can be expanded in an antigen-specific manner in vivo and in vitro and what conditions are required to establish the proliferation of Treg. Recent studies have shown that CD4 1 CD25 1 T cells can be expanded in vivo and in vitro upon antigen stimulation [37,38]. Moreover, CD4 1 CD25 1 Treg can be induced from CD4 1 CD25 -T cells [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…SJMHE1 is 66% identical to P277, a fragment of the human HSP60, which can arrest the spontaneous diabetogenic process in NOD mice [28]. Additionally, a sequence in SJMHE1 contained a random polymer of four amino acids (GLAT) also present in myelin basic protein that has been proven to be an effective treatment for MS [38,44]. Whether SJMHE1 can be used as a peptide-based therapy for allergic and autoimmune disease treatment requires further analysis.…”
mentioning
confidence: 99%
“…The D-stereoisomer of GA also effectively binds MHC class II on APCs, but does not suppress EAE suggesting there may be other mechanisms of action [73]. GA treatment may restore the function of regulatory T cells (Treg) thereby increasing suppression of autoreactive lymphocytes [74]. GA's effect on the adaptive immune system is not limited to T cell interactions, however.…”
Section: Mechanisms Of Actionmentioning
confidence: 99%